THE SIGNIFICANCE OF THE PRINCIPLE OF COMPLETENESS IN LEGAL CODIFICATION (Scientific Conference on Multidisciplinary Studies, 2025)
This article examines the principle of completeness in the context of legal codification, emphasizing its critical role in ensuring a coherent, accessible, and effective legal system. By analyzing historical and contemporary examples, the study highlights how the principle of completeness contributes to the stability and adaptability of codified legal systems.